Notes for a prehistory of research in history teaching (Clío & Asociados. La historia enseñada. ISSN: 2362-3063, 2025)
This paper aims to review the first steps of research into history teaching as a specific didactic approach since around 1980, establishing three stages: the didactic knowledge of innovative teachers, the initial steps of research at FLACSO, and the later flourishing in public universities. Concern about the shortcomings in the teaching of the subject and the backwardness of the content transmitted in the work of innovative teachers of the 1980s intensified and consequently acted as an incentive to raise the issue in the public eye. A significant element that later was added to this momentum was the process of continuous educational reforms that began with the approval of the Federal Education Law in 1993 and continued with the National Education Law in 2006. The constant processes of change and innovation during those years encouraged research.
Keywords: historical thought; specific didactics; didactic knowledge; research at FLACSO; public universities